Pengaruh Persepsi Kemudahan, Risiko, Literasi Digital terhadap Niat Penggunaan Coretax di Palembang - Ferli Herlan Lius; Kathryn Sugara (MDP Student Conference, 2026)
This study aims to analyze the effects of perceived ease of use, perceived risk, and digital literacy on the intention to use the Coretax system among corporate taxpayers in Palembang. This research employs a descriptive quantitative method using primary data collected through questionnaires distributed to respondents. The sample consists of 105 corporate taxpayers, determined using the Slovin formula. The respondent criteria include corporate taxpayers who have already used the Coretax system. Data collection was conducted by distributing questionnaires to actual users of the Coretax system. The results indicate that perceived ease of use and digital literacy have a significant effect on the intention to use Coretax, while perceived risk does not significantly affect the intention to use Coretax.